Surgery following neoadjuvant chemoradiation therapy in clinical N3 esophageal cancer results in improved survival: a propensity-matched analysis. Issue 7 (21st December 2020) - Alvarado, Christine E; Worrell, Stephanie G; Bachman, Katelynn C; Gray, Kelsey; Perry, Yaron; Linden, Philip A; Towe, Christopher W
Abstract: Esophageal cancer patients with extensive nodal metastases have poor survival, and benefit of surgery in this population is unclear. The aim of this study is to determine if surgery after neoadjuvant chemoradiotherapy (nCRT) improves overall survival (OS) in patients with clinical N3 (cN3) esophageal cancer relative to chemoradiation therapy (CRT) alone. The National Cancer Database was queried for all patients with cN3 esophageal cancer between 2010 and 2016. Patients who met inclusion criteria (received multiagent chemotherapy and radiation dose ≥30 Gy) were divided into two cohorts: CRT alone and nCRT + surgery. 769 patients met inclusion criteria, including 560 patients who received CRT alone, and 209 patients who received nCRT + surgery. The overall 5-year survival was significantly lower in the CRT alone group compared to the nCRT + surgery group (11.8% vs 18.0%, P < 0.001). A 1:1 propensity matched cohort of CRT alone and nCRT + surgery patients also demonstrated improved survival associated with surgery (13.11 mo vs 23.1 mo, P < 0.001). Predictors of survival were analyzed in the surgery cohort, and demonstrated that lymphovascular invasion was associated with worse survival (HR 2.07, P = 0.004). Despite poor outcomes of patients with advanced nodal metastases, nCRT + surgery is associated with improved OS. Of those with cN3 disease, only 27% underwent esophagectomy. Given the improved OS, patients with advanced nodal disease should be considered for surgery. Further investigation is warranted to determine which patients with cN3 disease would benefit most from esophagectomy, as 5-year survival remains low (18.0%).